A reliability analysis of a Malaysia jacket platform - Chin, Doris Chong Leng (2005)
After several decades of development, structural reliability technologies are maturing and becoming one of the essential assessment and design tools in the offshore industry. The objective of the thesis is to quantify the level of structural reliability of the jacket structure in the Malaysia waters. Offshore structural reliability analyses are dependent upon the environmental loads assumed to act on the structure. The modeling of environmental loading is based on the wave climate of Malaysia waters. The joint probability density function for the significant wave height and spectral peak period is modelled. Response of the structure under environmental loading was investigated by using the time domain simulation. Necessary simulation time steps are established. Interaction ratios of the members were computed based on the API RP2A-WSD to determine the level of stress utilisation of the members. From here, critical members of the jacket structure were identified. The probability failure of the critical members and other structural members of interest was determined by using the Hasofer and Lind reliability index. The fluctuation in loads and variation material properties were accounted in the assessment. For many cases failure of one component will not results in the collapse of the whole structure. Thus, system reliability analysis was carried out by using the pushover method. The system was modeled as series of parallel sub-system and the reliability of the system was evaluated by using the simple bound. The failure path of the structure was identified. Deterministic system effects of the structure were analyzed to study the redundancy of the structure, which were quantified by the reserve strength and the damage tolerance ratio. From here, the level of reliability of the jacket structure is quantified, and it serves as a reference for the evaluation of reliability-based design of jacket structures in Malaysia waters